(untitled) (Research, Society and Development, 2021)
The emergency contraceptive (EC) is a drug widely used by young women, also known as the morning-after pill and aims to prevent unintended pregnancy, a drug developed in the 70s. Women especially young women who use this medication know little about its pharmacodynamics, its main drug interactions and its adverse effects, and end up using it frequently, but it is worth remembering that it cannot be used frequently. The literature review article aims to understand the role of the pharmacist in the orientation and liberation of the indiscriminate use of the emergency contraceptive by young women, as well as to clarify on the adverse effects that this medication has in case of its use as conventional contraceptive. We conclude that EC is a drug that has proven to be effective in case of emergency if used within the established time frame, after unprotected sexual intercourse, but it is worth remembering that it should not be used frequently. The women and young people who use this medication know little about side effects, drug interactions of emergency contraception, the pharmacist is the health professional of great importance for the guidance so that women do not use EC frequently and use it correctly.